Does it matter where you come from? Vertical spillovers from foreign direct investment and the origin of investors. - Javorcik, B; Spatareanu, M (Elsevier, 2011)
This study uses firm-level panel data from Romania to examine whether the origin of foreign investors affects the degree of vertical spillovers from FDI. Investors' origin may matter for spillovers to domestic producers supplying intermediate inputs in two ways. First, the share of intermediates sourced locally by multinationals is likely to increase with the distance between the host and the source economy. Second, the sourcing pattern is likely to be affected by preferential trade agreements. In this case, the Association Agreement between Romania and the European Union (EU) implies that inputs sourced from the EU are subject to a lower tariff than inputs sourced from the United States or Canada. This means that on average American investors may have a greater incentive than EU investors to source from Romania and hence present a greater potential for vertical spillovers. The empirical analysis produces evidence consistent with this hypothesis. The results show a positive association between the presence of American companies in downstream sectors and the productivity of Romanian firms in the supplying industries and no significant relationship in the case of European affiliates. The results also indicate that Romanian firms in sectors whose products are expensive to transport benefit more from downstream presence of American affiliates than Romanian firms in sectors with low shipping costs. No such pattern is found for European affiliates.